Warriors : Graystripe's adventure - Hunter, Erin; Jolley, Dan (Warriors manga., 2017)
"Graystripe, deputy of ThunderClan, has been captured by Twolegs. He longs to go back to the forest and his Clan, and after he meets a feisty kittypet named Millie, they set off in search of his Clanmates. But with the forest destroyed, and no clear path to lead him, how will Graystripe find his way home?"--Back cover.